Nummulites and assilina from the Chachura formation, Baitadi district, Far West, Nepal (Journal of Nepal Geological Society, 2025)
The Tertiary Group in the Shivnath-Salena area is characterized by brown quartzite with black carbonaceous shale, siltstone, purple and grey shale, and green sandstone with a lenticular bed of grey limestone containing foraminifera. The present palaeontological study, in the type locality, contributes to the identification and understanding of the formation. Five species from the two genera of Nummulites and Assilina are identified from the Chachura Formation in Chachura Section, Far West Nepal. The larger foraminiferal species, Nummulites mamillatus, Nummulites globulus, Nummulites atacicus, Assilina granulate, and Assilina sp., have been identified. These faunal and facies assemblages indicate that the Chachura Formation was deposited in the shallow-shelf open marine environment in an Early–Middle Eocene age.